HIV Infection and older adults: a retrospective single-site cohort study from Johannesburg South Africa - Butler, India Lucy Claire (My University, 2017)
Human Immunodeficiency Virus (HIV) treatment in South Africa has had an inconsistent and controversial history. Presently South Africa is home to the largest number of HIV positive people and has the biggest antiretroviral program in the world. [No abstract provided. Information taken from Literature Review]
A research report submitted to the University of Witwatersrand, Johannesburg in fulfilment of the degree of Master of Medicine 2017.
Keywords: HIV